Implementasi Kebijakan Pengelolaan Inventaris Barang Bergerak Milik Daerah di Lingkungan Pemerintah Kota Palangka Raya - Muhamad Yusuf; Kobota Kobota (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This study aims to assess the implementation of the management policies for regional goods belonging to the region within the Palangka Raya City Government. The research focus is directed at efforts to answer research questions on how the implementation of moving inventory management policies belongs to the area of the Palangka Raya City Government. The research method used in this study is qualitative descriptive with primary data obtained from the results of observations, interviews, and documentation of the heads of SKPD, heads of SKPD Technical Implementation Units and Management Officers, Regional Property Storage of the City of Palangka Raya. The results showed that: 1) The implementation of the moving inventory management policy belonging to Palangka Raya City has not been running as it should have been dominantly caused/influenced by communication factors, and dispositions, while resource factors and bureaucratic structures also played a role but were not dominant. 2) The most common violation of the policy regarding the management of movable property belonging to the region is that movable property belonging to the Palangka Raya city area is carried out without procedures, either at the time of transfer or at full time